Lethal Methanol Poisoning: Correlation Between Autopsy, Toxicology, and Vitreous Biochemistry - Lokmane Dali Braham,; Abderrahmane Kori Yahia,; Feriel Hadji,; Souad Nagoudi,; Massinissa Benyagoub,; Rahmani lyna,; Nour El Yakine Keraghel,; Mohamed Amine Kerdoun,; Younes Zebbiche,; Djamil Azzouz,; Rachid Belhadj, (International Journal of Medical Toxicology and Legal Medicine, 2025)
Background: Methanol remains a frequent cause of fatal poisoning worldwide, especially in low-resource regions where ingestion of cologne or denatured alcohol is common. Postmortem diagnosis can be challenging because of overlapping features with ethanol intoxication and postmortem alcohol production. Case presentation: We report a fatal case of methanol intoxication in a 42-year-old man who ingested cologne. Autopsy revealed pulmonary and cerebral edema, visceral congestion, and petechial hemorrhages, consistent with a hypoxic mechanism of death. Toxicological analyses performed by direct-injection GC–MS identified methanol at 1.56–1.63 g/L in blood, 2.16 g/L in vitreous humor, and 6.23 g/L in urine, with formic acid concentrations reaching 0.8 g/L in blood and 5.3 g/L in urine. Ethanol was also detected (0.4–1.8 g/L), suggesting partial but insufficient inhibition of methanol metabolism. Thanatobiochemical analysis of vitreous humor using a rapid co-oximeter showed marked lactic acidosis (lactate = 9.68 mmol/L, under limite of detection, Na⁺ = 126.9 mmol/L, pH = 7.12), confirming ante-mortem metabolic collapse. Conclusion: The correlation between autopsy findings, toxicological results, and vitreous biochemistry provided conclusive evidence of fatal methanol poisoning. This case highlights the forensic importance of integrating thanatobiochemistry with multi-matrix toxicology to confirm methanol-related deaths and elucidate their metabolic mechanisms.